Tensor image enhancement and optimal multichannel receiver combination analyses for human hyperpolarized 13C MRSI. Issue 6 (5th June 2020) - Chen, Hsin‐Yu; Autry, Adam W.; Brender, Jeffrey R.; Kishimoto, Shun; Krishna, Murali C.; Vareth, Maryam; Bok, Robert A.; Reed, Galen D.; Carvajal, Lucas; Gordon, Jeremy W.; van Criekinge, Mark; Korenchan, David E.; et al.
Abstract : Purpose: With the initiation of human hyperpolarized 13 C (HP‐ 13 C) trials at multiple sites and the development of improved acquisition methods, there is an imminent need to maximally extract diagnostic information to facilitate clinical interpretation. This study aims to improve human HP‐ 13 C MR spectroscopic imaging through means of Tensor Rank truncation‐Image enhancement (TRI) and optimal receiver combination (ORC). Methods: A data‐driven processing framework for dynamic HP 13 C MR spectroscopic imaging (MRSI) was developed. Using patient data sets acquired with both multichannel arrays and single‐element receivers from the brain, abdomen, and pelvis, we examined the theory and application of TRI, as well as 2 ORC techniques: whitened singular value decomposition (WSVD) and first‐point phasing. Optimal conditions for TRI were derived based on bias‐variance trade‐off. Results: TRI and ORC techniques together provided a 63‐fold mean apparent signal‐to‐noise ratio (aSNR) gain for receiver arrays and a 31‐fold gain for single‐element configurations, which particularly improved quantification of the lower‐SNR‐[ 13 C]bicarbonate and [1‐ 13 C]alanine signals that were otherwise not detectable in many cases. Substantial SNR enhancements were observed for data sets that were acquired even with suboptimal experimental conditions, including delayed (114 s) injection (8× aSNR gain solely by TRI), or from challenging anatomy or geometry, as in the case of a pediatric patient with brainstem tumor (597× using combined TRI and WSVD). Improved correlation between elevated pyruvate‐to‐lactate conversion, biopsy‐confirmed cancer, and mp‐MRI lesions demonstrated that TRI recovered quantitative diagnostic information. Conclusion: Overall, this combined approach was effective across imaging targets and receiver configurations and could greatly benefit ongoing and future HP 13 C MRI research through major aSNR improvements.